Pengaruh Pertumbuhan Ekonomi, Investasi, Teknologi, Dan Upah Minimum Terhadap Kesempatan Kerja Di Kabupaten/Kota Provinsi Bali - Purvance, Jessica Athalia; Marhaeni, Anak Agung Istri Ngurah (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2023)
The purpose of this study is to (1) analyze the joint effects of economic growth, investment, technology and minimum wage on employment opportunities in districts/cities in Bali; (2) Analysis of partial effects of economic growth, investment, technology and minimum wage on employment opportunities in districts/cities in Bali. (3) Analyze the order of impact of economic growth, investment, technology and minimum wage on employment opportunities in districts/cities of Bali. This study is an associative quantitative study using panel data of up to 72 observations. Data sources for this study are secondary data from the Bali Provincial Central Bureau of Statistics and primary data obtained from informants through in-depth interviews. The collected data were then analyzed using several linear regression analysis techniques. Based on the analysis results, it is shown that (1) economic growth, investment, technology and minimum wage simultaneously have a great impact on employment opportunities in provinces/cities in Bali. (2) Economic growth and minimum wages can have a significant positive impact on employment opportunities in provinces/cities of Bali Province. Investments and technology may not affect employment opportunities in districts and cities in Bali. (3) Minimum wage has the greatest impact, followed by economic growth, investment and technology keyword: Economic Growth, Investment, Technology, Minimum Wage, Job Opportunities